Status and determinants of crop diversification: evidence from Indian States - Kumar, Chinmaya Ranjan; Nayak, Chittaranjan; Pradhan, Ashis Kumar (Letters in spatial and resource sciences, 2024)
Crop diversification is indispensable for the development of Indian agriculture. The present paper examines the cropping pattern and status of crop diversification across 28 Indian states. It uses a balanced panel for the period 2000-01 to 2015-16 for all the states and deploys a Panel Autoregressive Distributed Lag model to identify the determinants of crop diversification. The paper observes that diversification is higher in the southern and western parts of India than in the northern and eastern parts. The analysis finds that cropping intensity, gross state domestic product, rural road density, and operational holding have led to crop diversification. In contrast, credit, fertilizer, irrigation intensity, and electricity have led to crop concentration. Overall findings endorse crop diversification promotion to improve the livelihood and farm-level output at the macro level.